EFFECTIVE DELEGATION AND LEADERSHIP IN SOFTWARE MANAGEMENT - MIRKHAN , STAR DAWOOD; OMER , SKALA KAMARAN; RASHID, TARIK AHMED; ALI, HUSSEIN MOHAMMED; HAMZA, MAHMOOD YASHAR; NEDUNCHEZHIAN, POORNIMA (Journal of Duhok University, 2023)
Delegation and leadership are critical components of software management, as they play a crucial role in determining the success of the software development process. This study examined the relationship between delegation and leadership in software management and the impact of these factors on project outcomes. Results showed that effective delegation and transformational leadership styles can improve workflow, enhance team motivation and productivity, and ultimately lead to successful software development projects. The findings of this study have important implications for software management practices, as they suggest that organizations and software managers should prioritize the development of effective delegation and leadership practices to ensure the success of their software development initiatives. Further research is needed to explore the complex interplay between delegation and leadership in software management and to identify best practices for improving these processes.